PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR SISWA KELAS X MATERI ANIMALIA MAS AL JIHAD - Hayatun Salimah (FKIP Universitas Tanjungpura, 2022)
Conducted this research with the aimed of identify the effect of cooperative learning model type Talking Stick on the learning outcome of class X students animalia material MAS Al Jihad Pontianak City. Quasi experimental form of research and nonequivalent control group design. Saturated sampling is a technique applied in research, where class X B is chosen as the experimental class and class X C is chosen as the control class. The instrument used the multiple choice test 20 questions. With average experimental class learning outcome of 16.6 and a control class of 15.29. Obtained test result Mann Whitney Ucoun = 87.5 < Utable = 115, the conclusion there is the influence of experimental class students learning result applied cooperative learning model type Talking Stick with a value of effect size 0.88 classified high. Key Words: Talking Stick, learning outcome, animalia.